Endovascular treatment of very small ruptured intracranial aneurysms: complications, occlusion rates and prediction of outcome. (17th November 2012) - Starke, Robert M; Chalouhi, Nohra; Ali, Muhammad S; Penn, David L; Tjoumakaris, Stavropoula I; Jabbour, Pascal M; Gonzalez, L Fernando; Rosenwasser, Robert H; Dumont, Aaron S
Abstract : Objective: To assess predictors of outcome following endovascular treatment of small ruptured intracranial aneurysms (SRA). Methods: Between 2004 and 2011, 91 patients with SRA (≤3 mm) were treated at our institution. Multivariate analysis was carried out to assess predictors of endovascular-related complications, aneurysm obliteration (>95%), recanalization and favorable outcome (Glasgow Outcome Scale 3–5). Results: Endovascular treatment was aborted in nine of 91 patients (9.9%). Procedure-related complications occurred in eight of 82 patients (9.8%) of which five were transient and three were permanent. Three patients (3.7%) undergoing endovascular treatment experienced an intraprocedural aneurysm rupture. Three of nine patients (33.3%) treated with stent- or balloon-assisted coiling experienced periprocedural complications compared with five of 73 patients (6.8%) receiving only coils or Onyx (p=0.039). There were no procedural deaths or rehemorrhages. Rates of recanalization and retreatment were 18.2% and 12.7%, respectively. No factors predicted initial occlusion or recanalization. In multivariate analysis, pretreatment factors predictive of a favorable outcome included younger age (OR 0.94; 95% CI 0.91 to 0.99, p=0.017), larger aneurysm size (OR 3.4; 95% CI 1.02 to 11.11, p=0.045), Hunt and Hess grade (OR 0.38; 95% CI 0.19 to 0.75, p=0.005) and location (OR 5.12; 95% CI 1.29 to 20.25, p=0.02). When assessing treatment and post-treatment variables, vasospasm was the only additional covariate predictive of a poor outcome (OR 5.90; 95% CI 1.34 to 25.93, p=0.019). Conclusions: Most patients with SRA can be treated with endovascular therapy and have limited complications. Overall predictors of outcome for patients undergoing endovascular treatment of SRA include age, aneurysm size, Hunt and Hess grade, location and post-treatment vasospasm.